Effects of exercise interventions on subjective sleep quality in older adults: a systematic review and meta-analysis of studies using the Pittsburgh sleep quality index - Li, Yafan; Quan, Wei; Gao, Ziqi; Wang, Xinyi; Wang, Yaxin; Meng, Hongnan; Kang, Jianxin (Frontiers in Medicine, 2025)
ObjectiveIn accordance with the 2024 Physical Activity Guidelines, this study aimed to evaluate the effects of exercise interventions on subjective sleep quality in older adults and to explore the potential dose–response relationship.MethodsA systematic search was conducted in Web of Science, PubMed, Cochrane Library, Scopus, and Embase for randomized controlled trials (RCTs) published up to May 1, 2025. Meta-analysis was performed using R, with standardized mean differences (SMD) and 95% confidence intervals (95% CI) used to quantify effect sizes. Subgroup analysis, meta-regression, and nonlinear dose–response modeling were conducted.ResultsA total of 26 RCTs involving 2,189 elderly participants were included. The meta-analysis revealed that exercise interventions significantly improved subjective sleep quality [SMD = −2.46, 95% CI (−2.99, −1.93), p < 0.001]. The most pronounced effects were observed in interventions with session durations ≤30 min [WMD = −4.25, 95% CI (−5.49, −3.02)], low intensity [WMD = −2.79, 95% CI (−3.44, −2.14)], twice-weekly frequency [WMD = −2.52, 95% CI (−3.00, −2.04)], and intervention durations ≤8 weeks [WMD = −2.45, 95% CI (−2.99, −1.91)]. Meta-regression showed no significant linear associations between sleep outcomes and intervention duration, intensity, frequency, or length. A nonlinear “U-shaped” dose–response relationship was identified, with the optimal effect observed at approximately 527 MET·min/week [Hedges’ g = −0.82, 95% CI (−1.12, −0.52)].ConclusionLow-frequency, short-duration, and low-to-moderate intensity exercise interventions can effectively improve subjective sleep quality in older adults. Notably, even low-dose exercise can yield significant benefits.